At the Nook of the Eight Paths: Søren Kierkegaard as "Architect of Thought" - Longo, Giulia (Kierkegaard studies. Yearbook, 2025)
Due to its complexity and intricacy, Kierkegaard’s authorship can be considered a work of "linguistic architecture." In this paper I will show that a parallel can be drawn between the spiritual places and the physical places, such as landscapes, nooks, and buildings, starting from the early Gilleleje journals, which inspired the Otteveiskrog in "In Vino Veritas," and continuing with the later writings Works of Love and The Sickness unto Death , where the focus is on building and inhabiting a house. I will conclude my analysis by mentioning a built environment, the family tomb, which Kierkegaard had already planned in detail in 1846.